2015
DOI: 10.1007/s12311-015-0671-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotizability and Performance on a Prism Adaptation Test

Abstract: The susceptibility to hypnosis, which can be measured by scales, is not merely a cognitive trait. In fact, it is associated with a number of physiological correlates in the ordinary state of consciousness and in the absence of suggestions. The hypnotizability-related differences observed in sensorimotor integration suggested a major role of the cerebellum in the peculiar performance of healthy subjects with high scores of hypnotic susceptibility (highs). In order to provide behavioral evidence of this hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Moreover, contrary to our hypothesis regarding simple attention performance, we observed a negative relationship between hypnotizability and performance on a basic psychomotor number sequencing task, whereby the more hypnotizable subjects were, the more slowly they completed the sequence. Although hypnotizability has been shown to relate to cerebellar control of sensorimotor integration 70 , it is unlikely that the observed relationship is due to a www.nature.com/scientificreports/ www.nature.com/scientificreports/ substantial motor factor as neither visual scanning nor motor speed (i.e., TMT conditions 1 and 5, respectively) was significantly related to hypnotizability. The observed relationship might represent a cognitive difference in the processing speed of number stimuli at different levels of hypnotizability.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, contrary to our hypothesis regarding simple attention performance, we observed a negative relationship between hypnotizability and performance on a basic psychomotor number sequencing task, whereby the more hypnotizable subjects were, the more slowly they completed the sequence. Although hypnotizability has been shown to relate to cerebellar control of sensorimotor integration 70 , it is unlikely that the observed relationship is due to a www.nature.com/scientificreports/ www.nature.com/scientificreports/ substantial motor factor as neither visual scanning nor motor speed (i.e., TMT conditions 1 and 5, respectively) was significantly related to hypnotizability. The observed relationship might represent a cognitive difference in the processing speed of number stimuli at different levels of hypnotizability.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary research further suggests a possible role for the cerebellum in hypnotic suggestibility ( Santarcangelo and Scattina 2016 ). For example, highs appear to display less precise control of movement and posture by sensory re-afferences and absence of motor learning perhaps due to less efficient cerebellar control ( Menzocchi et al 2015 ). They also show paradoxical pain modulation following transcranial cerebellar anodal stimulation ( Bocci et al 2016 ).…”
Section: Recent Advances In Hypnosis Researchmentioning
confidence: 99%
“…These findings suggest that the Highs experienced the imagery of actions more effectively than the Lows and that, through imagery, cortical activation was increased due to hypnotic suggestion. Indeed, previous studies have shown that the central programs for motor control seem to be better updated in Highs than in Lows 34,35 , and it is likely that a better control of actions relies also on the ability to quickly and more effectively incorporate a hypnotist's suggestions.…”
Section: Discussionmentioning
confidence: 99%